THE INFLUENCE OF COMPENSATION, WORK DISCIPLINE, AND ACHIEVEMENT MOTIVATION ON EMPLOYEE PERFORMANCE - Rahmat Hidayat (Universitas Riau Kepulauan, 2020)
The business world is now prosecuted to create high employee performance for office development. The office must be able to build and improve performance within its environment. The most common problem is South Cikarang Office . Which is in the field of serving to the society and government is related to the motivation of achieving a decline resulting from bonuses and wages that are less the main factor of discipline in the work decreases. The types of research used are quantitative methods and the research is conducted in this research is done at South Cikarang Office . Located at the location of Jl. Jababeka II Industrial Area. Researchers set the population in this study are employees of the South Cikarang Village Office . And the population contained in South Cikarang Office . A number of 50 people. The results showed that partial compensation had no effect on the performance of the employees of the South Cikarang Office , this is shown from the results of the T count value of (- 1,023 and the T table value of (2,012). Work discipline has an effect on the performance of the employees of the Office of Rural Cikarang South as indicated resources by the results of the T count value greater than the TTable (2,046 2,012). Achievement Also has a signifivant positive effect toward employee performance and this is shown from the results of Tcount greater than Ttable (4,078 2,012) From the above statement it can be concluded that partially Work Discipline and Achievement Motivation on Employee Performance influences, While Compensation does not affect the performance of South Cikarang Office employers.